UJI LABORATORIUM DAN ORGANOLEPTIK STIK DAUN KELOR (MORINGA OLEIFERA) SEBAGAI PRODUK INOVASI CEMILAN SEHAT PADA ANAK PRA SEKOLAH - Resty Noflidaputri; Sri Rahayu Lestari (Maternal Child Health Care, 2021)
Moringa is a magical plant that has rich nutrient. It is expected to help overcome nutritional problems of children in Indonesia Indonesia still had nutritional problems in children, namely in 2018 there were 3.9% malnutrition and 13.8% malnutrition. This study aimed to determine the laboratory and organoleptic aspects of Moringa leaf sticks as a healthy snack innovation in pre-school children. This type of this study was descriptive analytic with the population was all school-age children in early childhood (PAUD) Nagari Durian Gadang with 72 people. By using purposive sampling, 20 respondents were chosen as the samples. The data were collected through a questionnaires and laboratory test results of Moringa leaf sticks. It was analyzed by univariate analysis. The results showed that 100 grams of Moringa leaf stick samples contained 43.5% carbohydrates, 23.5% total fat, 9.69% protein, 424 Kcal calories, 25.4 mg/kg iron, 912 mg/kg calcium. While the organoleptic test results showed that 70% of respondents liked the sticks of Moringa leaf powder, 75% did not like the color, 50% liked the aroma, 85% liked the texture and 65% liked the taste of healthy snacks from the Moringa leaf sticks. It can be concluded that Moringa leaf sticks was healthy snacks that can help meet the nutritional and nutritional needs of pre-school age children. It is hoped that all parties, especially people who have school-age children can take advantage of processed foods from Moringa leaf sticks as healthy snacks for children.Keywords : Laboratory, organoleptic, Moringa leaf sticksReferences : 29 (2010-2020)